Investigation on the physical layer security of massive MIMO with small cells - Bernardo, Neil Irwin M.
The primary design goal in cellular technology is to provide high data rate services to its customers while still maintaining energy-efficient transmission over the network. The road to move forward is through deployment of highly densified network topologies, such as massive MIMO and small cell networks. However, the growth in cellular capacity and the number of connected devices would also result in an increase of sensitive and classified data being exchanged over the network, thus making security a critical design aspect for future mobile networks. One promising idea is to exploit the physical layer (PHY) characteristics of these highly densified network topologies in order to enhance security, known as PHY security In this research, the PHY security of a heterogeneous network architecture that combines massive MIMO technology and small cell networks via spatial soft-cell approach was investigated. An optimization model was formulated that minimizes the total power consumption of the network while satisfying certain degree of PHY security and Quality-of-Service (QoS) requirement. Furthermore, the optimization model was extended (1) to develop a low-complexity and energy-efficient PHY security scheme and (2) to consider uncertainties in eavesdroppers' channel state information (CSI). We provide promising results showing that employing massive MIMO at the base station and placing multiple operator-deployed small cell nodes can significantly improve energy efficiency and capacity of the cellular network while providing an adequate level of security; this is possible even with die proposed low-complexity PHY security scheme or imperfect eavesdropper CSI case. The study is able to identify a trade-off between PHY security and energy-efficiency and how it is affected by other parameters.